2013
DOI: 10.4103/0971-9784.114258
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac surgery in a patient with severe thrombocytopenia: How low is too low?

Abstract: Platelets play a very important role in hemostasis, especially after cardiac surgery. Excessive bleeding after such surgery may lead to increased need for transfusion and its incumbent increase in post-operative morbidity and mortality. Although most cardiac surgeons will offer a surgical option to a patient with moderate thrombocytopenia (platelet count around 70 × 10 9 /L), successful cardiac surgery has not been reported in patients with significantly lower platelets counts (less than 40 × 10 9 /L). We repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 6 publications
0
7
2
Order By: Relevance
“…The idiopathic thrombocytopenic purpura, drug-induced thrombocytopenia, infections (rubella), and pseudo-thrombocytopenia are among the causes of thrombocytopenia. 3 …”
Section: Introductionmentioning
confidence: 99%
“…The idiopathic thrombocytopenic purpura, drug-induced thrombocytopenia, infections (rubella), and pseudo-thrombocytopenia are among the causes of thrombocytopenia. 3 …”
Section: Introductionmentioning
confidence: 99%
“…Even though platelet counts less than 1 lakh/µL in creases the risk of perioperative bleeding significantly, there have been reports of CABG being done with plate let counts as low as 19 000/cu.mm in cases of ITP [9]. Our patient had stable platelet counts between 60,000-70,000/cu.mm in the preoperative period.…”
Section: Discussionmentioning
confidence: 55%
“…Most of the reports in the literature of cardiac surgical procedures in patients with low platelet counts have been in the setting of idiopathic thrombocytopenic purpura and heparin-induced thrombocytopenia in adults. [89] There are only few reports of surgery in CCHD with severe thrombocytopenia as in this patient. Olgar et al [10] reported a case of thrombocytopenia (platelet count: 21,000/mm 3 ) in an 8-year-old girl with tricuspid atresia and pulmonary stenosis who underwent a shunt surgery with platelet support, after which the platelet count spontaneously increased to 1.78 lakhs/mm 3 , and there were no hemorrhagic complications noted.…”
Section: Discussionmentioning
confidence: 92%